The influence of leader relational energy on employee cognitive well-being: A moderated mediation model - Liu, Danping; Gui, Siyuan; Zhang, Bingran; Gao, Haiyin; Yu, Xiao; Wu, Miaoxuan (Frontiers in Psychology, 2023)
Employee health, satisfaction and well-being have become hot-button issues among human resource professionals, hiring managers and even executives in corporate C-suites. However, cognitive well-being, a key dimension of employee occupational well-being that significantly affects employee morale, efficiency and overall physical health, has received little attention. In the context of the increasing complexity of work, focusing on cognitive well-being can help employees solve problems and execute complex tasks successfully. Based on conservation of resource (COR) theory, this study extends understanding of the relationship between leader relational energy and employee cognitive well-being by probing the mediating role of work absorption and highlights the importance of co-worker relational energy as a key boundary condition for effective leader relational energy. The results of a three-wave time study in China showed that employee work absorption played a mediating role between leader relational energy and employee cognitive well-being. In addition, co-worker relational energy moderated the relationship between leadership relational energy and work absorption. This study provides novel insights into management practice for leaders to improve employee cognitive well-being.